Exploring the impact of digital twin technology in infrastructure management: a comprehensive review - Qiu, Shi; Zaheer, Qasim; Ali, Fahad; Wajid, Saif; Chen, Hualiang; Ai, Chengbo; Wang, Jin (Journal of Civil Engineering and Management, 2025)
This paper examines the role of Digital Twin Technology (DTT) in transforming infrastructure management, with a focus on sustainability. It highlights how advancements in Artificial Intelligence (AI), Building Information Modeling (BIM), and the Internet of Things (IoT) are driving the effectiveness of Digital Twins in real-world applications. Through detailed case studies, the paper showcases the practical benefits of DTT across various infrastructure sectors. It also evaluates current trends and strategies for enhancing DTT integration into infrastructure systems. The research reveals a striking 80% increase in DTT-related publications from 2019 to 2024, with Asia, particularly China, leading in contributions. The paper concludes by addressing the future potential, challenges, and risks of DTT, offering valuable insights for stakeholders aiming to optimize infrastructure management in the digital era.